The Importance of Understanding COVID-19: The Role of Knowledge in Promoting Adherence to Protective Behaviors - Miller, Lisa M. Soederberg; Gee, Perry M.; Katz, Rachael A. (Frontiers in Public Health, 2021)
Background. Past research suggests that knowledge supports- but strong illness expectations thwart- adoption of protective behaviors (e.g., handwashing). Strong illness expectations may place COVID-19 essential workers at risk. It is unclear, however, whether knowledge can moderate the negative effects of pessimistic illness expectations on protective behaviors. We test COVID-19 knowledge as a moderator of the effects of 1) pessimistic illness expectations and 2) essential worker status on adherence to protective behaviors. Methods: Participants (n=350) completed measures of knowledge, illness expectations, and protective behaviors. We used chi-square tests to examine associations between variables and logistic regressions to test the moderation models predicting adherence (low, high) while controlling for demographics. Results: Knowledge, illness expectations, and adherence were significantly associated with each other (p<.05). Essential workers had stronger illness expectations and lower knowledge than did nonessential workers (p<.001). Logistic regressions showed a nonsignificant Worker Status x Knowledge interaction (p=.59) but a significant Knowledge x Illness Expectations interaction (p<.05) indicating that those with strong illness expectations and low knowledge were disproportionately at risk of failing to adhere to recommended behaviors. Conclusions: Knowledge promotes protective behaviors by buffering the negative effects of pessimistic illness expectations. Essential workers are more likely to have low levels of knowledge with strong illness expectations, suggesting that educational policies may be warranted.